A Roadmap for Swedish Island Research – Previous Knowledge, Current Debates, and Imminent Research Gaps - Paulina Ines Rytkönen; Håkan Tunón; Margareta Bohlin; Marcus Box; Sune Fogelström; Lotten Hjelm; Sten-Åke Persson; Tommy Larsson Segerlind; Ulf Westerberg (Rural Landscapes: Society Environment History)
This study is the result of a participatory and collaborative project in which Swedish scholars and representatives of island organizations in Sweden set out to define what Swedish island research is and identify imminent research gaps. The article answers the following questions: 1) Which key research gaps can be identified in Swedish island research? 2) How can we relate Swedish island research to the international field of island research? The study is based on community based participatory research. Data was collected through a participatory process with workshops, webinars, and participatory activities in 2022. The main conclusion is that there is a democracy deficit affecting island development which is caused by the institutional structure in Sweden where island communities are mainly subordinated mainland municipalities, and a lack of island and archipelago policies.